Stage or size? The identity of anatomical and visual outcomes in stage 3 and stage 4 idiopathic macular holes after vitrectomy - Yanping Yu; Xida Liang; Zengyi Wang; Jing Wang; Biying Qi; Wu Liu (BMC Ophthalmology, 2023)
Abstract Background Several previous reports suggested that stage 4 idiopathic macular holes (IMHs) may exhibit lower rate of anatomical success and poorer functional results comparing with stage 3 IMHs, while some others showed no differences. Actually, few studies focused on comparison of prognosis between stage 3 and stage 4 IMHs. Our previous study found that IMHs of these two stages demonstrate similar preoperative characteristics, and this study aims to compare anatomical and visual outcomes of IMHs between stage 3 and stage 4, and tries to figure out the outcome-associated factors. Methods This retrospective consecutive case series reviewed 317 eyes with IMHs of stage 3 and stage 4 from 296 patients who underwent vitrectomy with internal limiting membrane peeling. Preoperative characteristics like age, gender, and hole size, and intraoperative interventions such as combined cataract surgery were evaluated. Outcome measures included the primary closure rate (type 1), best-corrected visual acuity (BCVA), foveal retinal thickness (FRT) and prevalence of outer retinal defect (ORD) at the last visit. The pre-, intra-, and post-operative information were respectively compared between stage 3 and stage 4. Results The preoperative characteristics and intraoperative interventions exhibited no significant differences between stages. With comparable follow-up durations (6.6 vs. 6.7 months, P = 0.79), IMHs of the two stages exhibited similar primary closure rate (91.2% vs. 91.8%, P = 0.85), BCVA (0.51 ± 0.12 vs. 0.53 ± 0.11, P = 0.78), FRT (134.8 ± 55.5 μm vs. 138.8 ± 60.7 μm, P = 0.58), and prevalence of ORD (55.1% vs. 52.6%, P = 0.39). IMHs, either < 650 μm or larger, exhibited no significant difference in outcomes between the two stages. However, smaller IMHs (< 650 μm) demonstrated higher rate of primary closure (97.6% vs. 80.8%, P < 0.001), better postoperative BCVA (0.58 ± 0.26 vs. 0.37 ± 0.24, P < 0.001), and thicker postoperative FRT (150.2 ± 54.0 vs. 104.3 ± 52.0, P < 0.001) comparing with larger ones regardless of stage. Conclusion IMHs of stage 3 and stage 4 exhibited considerable identity of anatomical and visual outcomes. In large IMHs, the hole size, instead of stage, may be more important for prediction of surgical outcomes and choice of surgical techniques.